Male germline development in the tammar wallaby, Macropus eugenii. Issue 3 (March 2021) - Ishihara, Teruhito; Griffith, Oliver W; Tarulli, Gerard A; Renfree, Marilyn B
Abstract : Male germ cells undergo two consecutive processes – pre-spermatogenesis and spermatogenesis – to generate mature sperm. In eutherian mammals, epigenetic information such as DNA methylation is dynamically reprogrammed during pre-spermatogenesis, before and during mitotic arrest. In mice, by the time germ cells resume mitosis, the majority of DNA methylation is reprogrammed. The tammar wallaby has a similar pattern of germ cell global DNA methylation reprogramming to that of the mouse during early pre-spermatogenesis. However, early male germline development in the tammar or in any marsupial has not been described previously, so it is unknown whether this is a general feature regulating male germline development or a more recent phenomenon in mammalian evolutionary history. To answer this, we examined germ cell nuclear morphology and mitotic arrest during male germline development in the tammar wallaby ( Macropus eugenii ), a marsupial that diverged from mice and humans around 160 million years ago. Tammar pro-spermatogonia proliferated after birth and entered mitotic arrest after day 30 postpartum (pp). At this time, they began moving towards the periphery of the testis cords and their nuclear size increased. Germ cells increased in number after day 100 pp which is the time that DNA methylation is known to be re-established in the tammar. This is similar to the pattern observed in the mouse, suggesting that resumption of germ cell mitosis and the timing of DNA methylation reprogramming are correlated and conserved across mammals and over long evolutionary timescales.